2007
DOI: 10.1105/tpc.106.048173
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Efflux at the Root Plasma Membrane: Identification of anArabidopsisExcretion Transporter

Abstract: Root NO 3 À efflux to the outer medium is a component of NO 3 À net uptake and can even overcome influx upon various stresses. Its role and molecular basis are unknown. Following a functional biochemical approach, NAXT1 (for NITRATE EXCRETION TRANSPORTER1) was identified by mass spectrometry in the plasma membrane (PM) of Arabidopsis thaliana suspension cells, a localization confirmed using a NAXT1-Green Fluorescent Protein fusion protein. NAXT1 belongs to a subclass of seven NAXT members from the large NITRAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
167
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 82 publications
(143 reference statements)
3
167
0
2
Order By: Relevance
“…Recently, the Arabidopsis NPF7.3/NRT1.5 was shown to be a K + transporter and to NO 3 − -dependently control K + homeostasis in shoots (Drechsler et al 2015;Li et al 2017). Other family members, for example, function as a NO 3 − excretion transporter or in actinorhizal and rhizobial N-fixing symbioses (Jeong et al 2004;Segonzac et al 2007;Yendrek et al 2010), whereas a role of NPF proteins in plant-AMF interactions has not been observed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Arabidopsis NPF7.3/NRT1.5 was shown to be a K + transporter and to NO 3 − -dependently control K + homeostasis in shoots (Drechsler et al 2015;Li et al 2017). Other family members, for example, function as a NO 3 − excretion transporter or in actinorhizal and rhizobial N-fixing symbioses (Jeong et al 2004;Segonzac et al 2007;Yendrek et al 2010), whereas a role of NPF proteins in plant-AMF interactions has not been observed yet.…”
Section: Introductionmentioning
confidence: 99%
“…16 Thus, the physiological role of LATD/NIP, which is required for meristem function and rhizobium infection, is likely to be quite different from that of the characterized members of clade IV.…”
Section: Latd/nip Encodes a Putative Transporter Of The Nrt1(ptr) Familymentioning
confidence: 99%
“…Of the 19 Arabidopsis NRT1(PTR) members that fall into this clade, only 3, NRT1.6, NRT1.7 and NAXT1, have a biochemically demonstrated function: all are low-affinity nitrate transporters. [14][15][16] Clade IV includes one of the most closely related Arabidopsis NRT1(PTR) members to LATD/NIP, encoded by At1g52190, which has been reported in a review to be a low-affinity nitrate transporter, 6 but the data are unpublished. The physiological roles of these proteins are likely to be quite diverse as they each have a distinct tissue-specific expression pattern.…”
Section: Latd/nip Encodes a Putative Transporter Of The Nrt1(ptr) Familymentioning
confidence: 99%
“…It has been established that nitrate uptake by plants is an active, H + -coupled process facilitated through the highand low-affinity transport systems (HATS and LATS) which could be constitutive or inducible (Glass and Siddiqi 1995;Glass et al 2001Glass et al , 2002Zhao et al 1999;Tischner 2000;Touraine and Gojon 2001;Forde 2002). Also the nitrate influx into vacuole (Blumwald and Poole 1985;Schumaker and Sze 1987;Kabała et al 2003;de Angeli et al 2006;von der Fecht-Bartenbach et al 2010) as well as its efflux out of the plant cell (Segonzac et al 2007;Lin et al 2008) have been shown to be driven by a proton motive force. Active nitrate transport across plant cell membranes has been attributed to three families including the proton-coupled symporters and antiporters belonging to NRT1, NRT2 (Tsay et al 2007) and CLC multigenic families (de Angeli et al 2006Angeli et al , 2009von der Fecht-Bartenbach et al 2010).…”
Section: Introductionmentioning
confidence: 99%